Legal position of personal guarantee in security law - Irawan Soerodjo; Putra Hutomo (Trigin Publisher, 2023)
One of the essential elements of bank credit is the existence of a trust from the bank as a creditor to borrowers as debtors. This trust arises due to the fulfillment of all terms and conditions for obtaining bank credit by the debtor, including the clarity of the credit allocation, the existence of collateral or collateral. The object of collateral is an object or material right given by the debtor to the creditor to create confidence that the debtor will fulfill obligations that can be valued in money arising from an agreement. The research method in this writing is to use a normative legal approach, using a normative juridical approach, including reviews and variousanalysis legal materials and legal issues related to the problem being analyzed. The purpose of this research is to know the position of personal guarantee (personal guarantee) will appear, after the debtor does not fulfill the obligations in his engagement as appropriate (default). The results and conclusions of the research show that 1) Personal guarantees appear when the debtor defaults, replacing the debtor's position. 2) The creditor can ask the court for confiscation of property if the guarantor is uncooperative. 3) Articles 1831-1850 of the Civil Code link the guarantor and the debtor.